(untitled) (Global Journal of Human-Social Science, 2014)
In this paper, an attempt is made to discuss the origin and evil effects of Ebola epidemics in our society. It also examined the importance of exploring Biblical solutions to end the scourge of Ebola. The discourse relies on written materials, Holy Bible as well as oral testimonies. The paper revealed that the outbreak of Ebola could be a direct punishment for not following strictly the Biblical instructions that had warned against the avoidance and eating of certain animals, birds and foods. The words and instructions given to the Israelites then were not only relevant in this generation but equally provide a pattern for physical, spiritual and moral healthy living in our time. Though, man may not always understand the wisdom of God’s law but by obeying and adhering strictly to them, one would surely thrive. Hence, the work noted that apart from seeking medical solutions to the problem, the secular world need to recognize that reading, studying and applying the biblical instructions are the major preventive measures and cure that could be explored for any hopeless and terrible case like Ebola.